PENGARUH DANA DESA TERHADAP INDEKS PEMBANGUNAN MANUSIA (STUDI KASUS PADA PEMERINTAH KABUPATEN DI PROVINSI SUMATERA SELATAN) TAHUN 2017-2024 - Agresta Marsanda; Lisa Hermawati; Andri Irawan (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2025)
Village Funds and the Human Development Index are related to each other. In this study, the author wants to see whether the Village Fund received by each Regency can affect the increase in the Human Development Index in that Regency. This research uses quantitative research methods and panel data regression analysis. This research data is in the form of secondary data obtained through the official website of the ministry of finance and the official website of the central statistics agency. The result of this study is that the Village Fund Variable has a positive effect on increasing the Human Development Index in the Regency of South Sumatra Province in 2017-2024.